2023
DOI: 10.3892/wasj.2023.197
|View full text |Cite
|
Sign up to set email alerts
|

Biological applications of imiquimod analogues: An update (Review)

Abstract: The last decade witnessed intensive efforts in drug discovery and the emergence of thousands of molecules with potential for use as therapeutic targets. However, only a few hundred of these molecules reached the stage of clinical trials, with only a handful being translated from the bench to bedside. One such example is imiquimod, an immune response modifier belonging to the imidazoquinoline family. Imiquimod was first approved by the US Food and Drug Administration for the topical treatment of anal and genita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 112 publications
(170 reference statements)
0
2
0
Order By: Relevance
“…Imiquimod, which is also called R-837 or S-26308, was first approved by the US Food and Drug Administration (USFDA) for the treatment of anal and genital swellings or warts. Later, it was found that it possesses anticancer activity . Imiquimod is a Toll-like receptor ligand, used to treat different types of cutaneous malignancies .…”
Section: Therapeutic Strategies For the Treatment Of Skin Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…Imiquimod, which is also called R-837 or S-26308, was first approved by the US Food and Drug Administration (USFDA) for the treatment of anal and genital swellings or warts. Later, it was found that it possesses anticancer activity . Imiquimod is a Toll-like receptor ligand, used to treat different types of cutaneous malignancies .…”
Section: Therapeutic Strategies For the Treatment Of Skin Cancermentioning
confidence: 99%
“…Later, it was found that it possesses anticancer activity. 171 Imiquimod is a Toll-like receptor ligand, used to treat different types of cutaneous malignancies. 172 Recently, researchers proved that imiquimod promotes programmed cell death and autophagic cell mortality by inducing mitochondria-mediated apoptosis and ER-stress/PERK/PKR axis via an increasing ROS in SC cells.…”
Section: Therapeutic Strategies For the Treatment Of Skin Cancermentioning
confidence: 99%